Nutrient Profiling Model Towards Recommendation of A Healthy Diet: A Scoping Review - Salleh, Ruhaya; Rajikan, Roslee; Shahar, Suzana; Shahril, Mohd Razif; Elias, Siti Masitah; Ahmad, Noor Ani (Jurnal Gizi dan Pangan, 2023)
The objective of this study is to identify the availability of Nutrient Profiling (NP) models worldwide and discuss their application. This scoping review is based on the Preferred Reporting Items for Systematic Review and Meta-Analyses Extension for the Scoping Review (PRISMA-ScR) and the Arksey and O’Malley framework. Articles related to NP among adults published from 2012 to 2022, written in English, were retrieved from the Web of Science, Science Direct, Scopus, and Pubmed databases. Mendeley software was used for database acquisition and MS Excel for the syntesis process. Only 17 articles out of 2,019 article titles identified met the inclusion criteria for the review. This review discovers that the applications of NP in nutrition policies include food labelling, Front-Of-Pack (FOP), and regulations on food marketing, health, and nutrition. Fibre is the nutrient that needs to be included in the NP application compared to saturated fats, fatty acids, sodium, and total sugar. This scoping review demonstrates the scientific basis of the NP model’s development in public health policy, leading to advocacy and the recommendation of healthy diets.